PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING BERBANTUAN CROSSWORD PUZZLE PADA MATA PELAJARAN IPAS TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 102 PALEMBANG - Nurul Aini; Sukardi; Nugroho N. A. D (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether or not ther is an influence of the cooperative learning model assited by crossword puzzle in the natural and social science subject on the learning motivation of 4th grade students at SD Negeri 102 Palembang. The method used is an experimental method with the design form used in the form of One Group Pretest Posttest Design. The research sample taken in this study was Purposive Sampling. Data collection techniques using questionnaires to determine student learning motivation and documentation. The data analysis techniques used were Shapiro-Wilk in the normality test, homogeneity test, and Paired Sample T-Test in the hypothesis test. The results of the study showed that learning motivation in the posttest had a significant increase from the pretest, with the results of learning motivation in the posttest in the high category (27 students), and medium (3 students) with a total score of 1.720 and the average score was 57. In the pretest in the high category (7 students), medium (11 students), and low (12 students) with a total score of 1,169 and the average score was 38,96. Based on data analysis and discussion in this study, it can be concluded that: There is a significant influence of the cooperative learning model assisted by crossword puzlle in the natural and social science subject on the learning motivation of 4th grade students at SD Negeri 102 Palembang